The Morphogenesis of an Umbraquult Soil in forests of Kalimpong Himalayas, West Bengal - Banerjee, A. K. (Indian Forester, 1976)
The present paper deals with a profile belonging to the order umbraquult, exposed at 2700 m elevation in the forest area of Kalimpong Forest Division, West Bengal. The soil has an organic matter enriched epipedon underlain by an argillic horizon. The base rock is granite-gneiss. The study of the texture and the graphs representing the size distribution of the non-clay fraction indicates that the profile is developed from a uniform parent material. Intensive weathering resulting in paucity of heavy minerals has taken place in the entire profile. The pH and texture and micromorphological studies showed that the soil had the maximum weathering and evacuation of ion in the B 22t layer while the clay accumulation by illuviation was maximum at B 3t layer. The lateral water movement due to steep gradient may be an important factor to bring about the clay profile of the soil.